Elevated mean platelet volume predicts poor prognosis in colorectal cancer - Li, Na; Yu, Zhiwei; Zhang, Xin; Liu, Tiemin; Sun, Yu-xiang; Wang, Rui-tao; Yu, Kai-jiang (Scientific reports, 2017)
Altered mean platelet volume (MPV) is implicated in several malignancies. However, the clinicopathological significance and prognostic value of MPV in colorectal cancer (CRC) is still elusive. The purpose of this study was to elucidate the predictive significance of MPV in CRC. The retrospective study recruited 509 consecutive CRC patients between January 2009 and December 2009. The relationships between MPV and clinicopathological characteristics were analyzed. Kaplan-Meier method and Cox regression were used to evaluate the prognostic impact of MPV. Of the 509 CRC patients, high MPV levels were detected in 150 (29.5%) patients. Elevated MPV was associated with tumor differentiation (p < 0.001). Patients with increased MPV had poor overall survival compared with those with normal level (60.0% vs. 83.6%, log-rank test, p = 0.035). Cox regression analysis showed that MPV was an independent prognostic factor in CRC (HR = 1.452, 95% CI = 1.118–1.884, p = 0.005). In conclusion, MPV is easily available in routine blood test. Elevated MPV might act as a marker of prognosis and therapeutic target for CRC.